Membongkar Rasionalitas: Pemikiran Amartya Sen tentang Kekuasaan Ekonomi - Runesi, Wilhelmus F. N. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2022)
Discussing about rationality is often releated to human actions, because humans are considered as rationalist creatures who act to realize and decide things with their thinking abilities. The question is whether the society is becoming less critical in seeing the political games played by the power elite, or the authorities are using power to create fear by spreading some rationalizing concepts in such a way that they are accepted as truth. By tracing Amartya Sen’s thoughts, the author of this article tries to show the initial position (arche) of economics as a moral science, which seems to have been poisoned by desires for self-interest only. This article tries to reveal the fallacy of rationality behind the policies that have been used to implement power, which in this case have been promulgated by the government regarding economics in order to overcome various social and humanitarian problems such as poverty, hunger, and injustice in the society.